A framework for a net environmental benefit analysis based comparative assessment of decommissioning options for anthropogenic subsea structures: A North Sea case study - Nicolette, Joseph P.; Nelson, Nicholas A.; Rockel, Michael K.; Rockel, Mark L.; Testoff, Alex N.; Johnson, Larry L.; Williamson, Laura D.; Todd, Victoria L. G. (Frontiers in Marine Science, 2023)
The United Kingdom (UK) North Sea offshore oil and gas (O&G) exploration and production ( E&P) industry is expected to incur offshore subsea asset decommissioning costs of £30–75 billion (or more) over the next 30 years, representing significant current liabilities to the environment, taxpayers, and operators. Consequently, decommissioning is at the forefront of industrial, governmental, and non-governmental agendas. The removal of end-of-life structures is a highly complex activity with health, safety, environmental, social, economic, and technical implications; however, increasing scientific evidence supports that manmade subsea structures create hard, artificial, reef habitats that provide ecological and social benefits (i.e., ecosystem services) for the public. Given the significant uncertainty regarding how subsea structures should be retired at the end of their operational lifetimes, it is necessary for taxpayers and operators to understand the risks and benefits associated with potential decommissioning options. Currently, the North Sea decommissioning process is based on the requirements of the Oslo and Paris Convention’s (OSPAR) Decision 98/3 and O&G UK regulations, which follow comparative assessment (CA) multiple-criteria decision analysis (MCDA) guidelines to determine the best overall strategy for decommissioning of structures. However, CA MCDA processes can be biased, ambiguous, and overly complicated, difficult to use, interpret, and replicate, and limited in their consideration of multigenerational benefits. Therefore, to assist decision-makers in understanding and evaluating options and associated benefits for decommissioning subsea structures, this study adapted the net environmental benefit analysis (NEBA) framework to supplement and strengthen the CA process for evaluating decommissioning options for offshore O&G facilities. The NEBA-CA approach addresses the growing need for a quantitative, scientifically robust, defendable, and transparent MCDA approach to determine optimized decommissioning strategies for subsea assets. Using a North Sea case study, this work demonstrates the ability of NEBA-CA to resolve inherent complexity in comparing decommissioning options. NEBA-CA graphically charts outcomes that effectively and simply communicate relative differences in quantified, multigenerational benefits and risk metrics associated with credible decommissioning alternatives. NEBA-CA thereby supports operators and regulators to decommission assets in a way that documents maximizing ecosystem service benefits for the public while managing site-related navigational, trawling, stability, and decommissioning option implementation risks.